2021
DOI: 10.1007/s15010-021-01723-5
|View full text |Cite
|
Sign up to set email alerts
|

Analytical performance of the point-of-care BIOSYNEX COVID-19 Ag BSS for the detection of SARS‐CoV‐2 nucleocapsid protein in nasopharyngeal swabs: a prospective field evaluation during the COVID-19 third wave in France

Abstract: Background The accuracy and reliability of rapid diagnostic tests are critical for monitoring and diagnosing SARS-CoV-2 infection in the general population. This study aimed to evaluate the analytical performance of the BIOSYNEX COVID-19 Ag BSS (Biosynex Swiss SA, Fribourg, Switzerland) antigen rapid diagnostic test (BIOSYNEX Ag-RDT), which targets the SARS-CoV-2 N-nucleocapsid protein for the diagnosis of COVID-19. The Ag-RDT was compared with a real-time RT-PCR (rtRT-PCR) as gold standard for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(27 reference statements)
0
4
0
Order By: Relevance
“… In patients with signs and symptoms compatible with COVID-19, we suggest the use of laboratory based NAAT in nasopharyngeal samples versus rapid antigen detection testing in nasopharyngeal samples for the diagnosis of COVID-19. Weak against Very low [ 4 , 5 , 16 , 106 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , 6 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , 8 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , 10 , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , 11 , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ...…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%
See 2 more Smart Citations
“… In patients with signs and symptoms compatible with COVID-19, we suggest the use of laboratory based NAAT in nasopharyngeal samples versus rapid antigen detection testing in nasopharyngeal samples for the diagnosis of COVID-19. Weak against Very low [ 4 , 5 , 16 , 106 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , 6 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , 8 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , 10 , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , 11 , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ...…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%
“… In patients ≥ 12 years old with signs and symptoms compatible with COVID-19, we suggest the use of laboratory-based NAAT versus rapid antigen detection testing for the diagnosis of COVID-19. Weak against Low [ 4 , 6 , 25 , 28 , 33 , 34 , 37 , [41] , [42] , [43] , [44] , 46 , 7 , 48 , 49 , [53] , [54] , [55] , [62] , [63] , [64] , 70 , 71 , 10 , 77 , 82 , 83 , 90 , 94 , 108 , 109 , 111 , 113 , 115 , 11 , 116 , 119 , 123 , 128 , 130 , 133 , [135] , [136] , [137] , 140 , 17 , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , ...…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus pandemic 2019 (COVID-19) quickly became a worldwide public health crisis and continues to spread worldwide. 1 , 2 In recent times, the study of long COVID, especially brain complications, has been intensely investigated. 3 , 4 Some studies have shown that severe COVID-19 infection could lead to white matter hyperintensities (WMHs).…”
Section: Introductionmentioning
confidence: 99%